Biodegradação da vinhaça resíduo da produção de etanol - Francisco, Gabriela Amorozo [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
The State of São Paulo is responsible for the largest sugar cane production in Brazil, as well as the largest production of ethanol made of this raw material – which is widely used as fuel for automobiles. This utilization began in the 1970’s, with the institution by the Brazilian government of the National Alcohol Program (PRO-ÁLCOOL), as a consequence of the petroleum crisis, rising again five years ago, with the development of flex fuel cars. The obtaining process of ethanol originates residues; amongst them, vinasse is the one that’s generated in the largest amount (an average of 10 to 13 litres/litre of ethanol produced). The disposal of this residue in waters was only forbidden in 1978, but before that, researchers had already been investigating its utilization as raw material. This paper had the objective of accompany the biodegradation of vinasse by evaluating the oxygen comsumption during it until the ultimate Biochemical Oxygen Demand (uBOD), performed in twenty days; another objective was to analyse the biomass production of Saccharomyces cerevisae in this residue. Physical and chemical analyses of the residue were also performed, as well as acute toxicity essays using Daphnia similis and Dugesia tigrina, before and after its biodegradation. The physical and chemical analyses pointed elevated acidness (pH = 3,98), conductivity (8,30 mS/cm) and COD (25.693,43 mg O2/L) and mean quantity of suspended solids (5.246 mg/L). The toxicity essays indicated absence of toxic potential in vinasse after biodegradation for both species. The uBOD degradated until 88,22% of the COD, demonstrating the possibility of biodegradation of most of the residue’s organic load in a relatively short period of time. S. cerevisae caused a 37,03% COD diminution in vinasse, diminished its conductivity and promoted a slight elevation of the pH; it obtained low biomass...(Complete abstract click electronic access below)

O Estado de São Paulo é, atualmente, o maior produtor de cana-de-açúcar do Brasil, assim como do etanol proveniente dessa matéria-prima – amplamente utilizado como combustível de veículos automotores. Esta utilização teve início na década de 1970, com a instituição pelo governo brasileiro do Programa Nacional do Álcool (PRO-ÁLCOOL), em virtude da crise do petróleo, e voltou a crescer nos últimos cinco anos, com o desenvolvimento dos veículos bicombustíveis (carros “flex fuel”). O processo de obtenção do etanol origina resíduos; dentre eles, a vinhaça é gerada em maior quantidade (em média, de 10 a 13 litros/litro de etanol produzido). O descarte desse resíduo em corpos hídricos só foi proibido em 1978, porém antes disso, pesquisadores já vinham investigando sua utilização como matéria prima. Este trabalho teve por objetivo acompanhar a biodegradação da vinhaça mediante avaliação do consumo de oxigênio até a Demanda Bioquímica de Oxigênio última (DBOu), realizada em vinte dias, além de analisar a produção de biomassa de Saccharomyces cerevisae neste resíduo. Foram realizadas também análises físicas e químicas do resíduo, assim como testes de toxicidade aguda com Daphnia similis e Dugesia tigrina antes e depois da sua biodegradação. As análises físicas e químicas indicaram acidez (pH = 3,98), condutividade (8,30 mS/cm) e DQO (25.693,43 mg O2/L) elevadas e quantidade mediana de sólidos em suspensão (5.246 mg/L). Os testes de toxicidade indicaram ausência de potencial tóxico da vinhaça após a biodegradação para ambas as espécies. A DBOu degradou até 88,22% da DQO, demonstrando a possibilidade de biodegradação da maior parte da carga orgânica do resíduo em tempo relativamente curto. O cultivo de S. cerevisae apresentou diminuição...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Cana-de-açúcar; Biodegradação; Etanol - produção; Vinhaça; Ethanol - production